Kesalahan Fonologi Presenter pada Mobile Legends: Bang Bang Indonesia - M Katowi Ramadhani; Suyanu Suyanu; Burhanuddin Burhanuddin (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2020)
This study aims to determine the phonological errors made by the presenter of Mobile Legends: Bang Bang Indonesia. This research is a descriptive study that uses a qualitative approach so that this research can be achieved, the data collection method is used in the form of the observation method with note-taking techniques, while the method used in analyzing data is the high method with the dressing technique. The results of this study indicate that the phonological errors uttered by the presenter are as follows: (1) errors in the vowel sound / a / amount to 45 errors, (2) vowel sounds / i / are 4 times the error, (3) vowel sounds / u / amounted to 2 errors, (4) vowel sounds / ə / totaled 7 errors, (5) errors in diphthong / ai / amounted to 12 errors, (6) diphthong / au / totaled 12 times errors, (7) sound errors consonants / h / amounted to 9 errors, (8) sounds / k / amounted to 30 errors, (9) sounds / m / amounted to 1 error, (10) sounds / s / amounted to 21 errors, and (11) sounds / z / amount to 1 error. Keywords: phonological error, presenter, language error.